Association between E mitral point septal distance and left ventricular end diastolic diameter in healthy dogs (Veterinary Science, 2017)
The separation distance of the mitral E point to the septum (EPSS) is one of the echocardiography parameters used to assess the degree of dilation eccentric supporting the left ventricle. The end-diastolic diameter (DVID) of this unit increases as the size and weight in normal canine increase. This paper aims to analyze the association between the EPSS and DVID distance in a population of healthy dogs aware of how to assess the correlation between the two variables presented. 159 dogs, 80 males and 79 females, 107 whole and 52 geldings of various ages, sizes and body weight were selected. The sample was divided into 5 groups according to body weight: Group I: 1-10kg (N=43), Group II: 10-20kg (N=39), Group III: 20-30kg (N=38), Group IV: 30-40kg (N=27) and Group V: 40-50kg (N=12). All dogs had a body condition score between 2.5 - 3.5. The mean and standard for EPSS diverted and DVID away were, respectively: Group I: 0.53mm ±2.11 - 25.08mm ±3.29, Group II: 0.68mm ±3.00 - 32.85mm ±4.09, Group III: ± 3.93mm 0.59 - 39.09mm ±3.21; Group IV: 0.74mm ±4.43 - 42.89mm ±3.04; Group V: 0.68 ±5.18mm - 47.84mm ±4.38. The observed association between the two variables showed a positive linear correlation (r=0.80 – r2=0.61 - p
Keywords: Canines; correlation; echocardiography; EPSS y DVID.